Introducing a nested phase change agent with an acoustic response that depends on electric field: A candidate for myocardial perfusion imaging and drug delivery. (September 2018) - Cimorelli, Michael; Angel, Brett; Fafarman, Aaron; Kohut, Andrew; Andrien, Benjamin; Barrett, Kyle; Wrenn, Steven
Abstract: We present a voltage-sensitive phase change agent comprising an aqueous emulsion of surfactant-coated liquid perfluorocarbon droplets nested within a negatively charged phospholipid bilayer. The sensitivity to voltage allows, via exposure to an electric field, acoustic activation of the perfluorocarbon droplets at an ultrasound intensity that is otherwise insufficient to cause activation. The result is a phase change agent for which activation depends not on ultrasound intensity but rather on the presence of an electric field. Accordingly, we offer the first enhanced ultrasound contrast agent ("Electrast") that takes advantage of the electrical activity of the heart and leads to selective activation at a fixed mechanical index (MI). Being voltage-sensitive, Electrast activates selectively in the coronary circulation, giving enhanced ultrasound contrast within the myocardium while leaving other regions largely unenhanced. Specifically, in a closed chest swine study, the contrast enhancement between the myocardium and the left ventricle increased by 36.4 dB ±0.2 upon injection of a charged, nested PCA formulation at a fixed MI of 0.9 (GE Vivid i ). Similar enhancement was observed in rats, and the contrast-to-tissue ratio increased by nearly 10 dB at an MI of 0.28 upon exposure to an electric field of 1 V/cm in a tissue-mimicking phantom. Additionally, ultrasound-induced leakage of calcein, a water-soluble fluorescent dye, from a nested, charged PCA formulation more than doubled at a peak negative pressure of 0.5 MPa upon exposure to an electric field of 0.25 V/cm. These results suggest that Electrast, a voltage-sensitive phase change agent, is a candidate for myocardial perfusion imaging using ultrasound.